The Impact of Deep Y Descent on Hemodynamics in Patients With Heart Failure and Preserved Left Ventricular Systolic Function - Daisuke Harada; Hidetsugu Asanoi; Takahisa Noto; Junya Takagawa (Frontiers in Cardiovascular Medicine, 2021)
Background: Influence of right ventricular diastolic function on the hemodynamics of heart failure (HF). We aimed to clarify the hemodynamic features of deep Y descent in the right atrial pressure waveform in patients with HF and preserved left ventricular systolic function.Methods: In total, 114 consecutive inpatients with HF who had preserved left ventricular systolic function (left ventricular ejection fraction ≥ 50%) and right heart catheterization were retrospectively enrolled in this study. The patients were divided into two groups according to right atrial pressure waveform, and those with Y descent deeper than X descent in the right atrial pressure waveform were assigned to the deep Y descent group. We enrolled another seven patients (two men, five women; mean age, 87 ± 6) with HF and preserved ejection fraction, and implanted a pacemaker to validate the results of this study.Results: The patients with deep Y descent had a higher rate of atrial fibrillation, higher right atrial pressure and mean pulmonary arterial pressure, and lower stroke volume and cardiac index than those with normal Y descent (76 vs. 7% p < 0.001, median 8 vs. 5 mmHg p = 0.001, median 24 vs. 21 mmHg p = 0.036, median 33 vs. 43 ml/m2p < 0.001, median 2.2 vs. 2.7 L/m2, p < 0.001). Multiple linear regression revealed a negative correlation between stroke volume index and pulmonary vascular resistance index (wood unit*m2) only in the patients with deep Y descent (estimated regression coefficient: −1.281, p = 0.022). A positive correlation was also observed between cardiac index and heart rate in this group (r = 0.321, p = 0.038). In the other seven patients, increasing the heart rate (from median 60 to 80/min, p = 0.001) significantly reduced the level of BNP (from median 419 to 335 pg/ml, p = 0.005).Conclusions: The hemodynamics of patients with HF with deep Y descent and preserved left ventricular systolic function resembled right ventricular restrictive physiology. Optimizing the heart rate may improve hemodynamics in these patients.